Pengaruh Perekonomian Mikro dan Makro terhadap Pertumbuhan Ekonomi Indonesia - Yani, Ayu Syah Fitri; Ruslan, Dede (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Finding out how the macro and micro economies affect Indonesia's economic growth is the aim of this study. The problem with the national economy is the scope of macroeconomics. There will surely be difficulties when a country's economy expands. The nation's state governments must address that impediment since it is an internal problem. The problems of inflation and unemployment cannot be separated from the problems of Indonesia's population size and quality due to a variety of obstacles. Of course, an autonomous nation implements its policies to deal with these problems. Whether a policy is successful or not, it is something to aim for. A skilled labor force capable of importing and exporting goods that can make the nation visible to the rest of the world can support the country's economic growth.